Seasonal cycle, size dependencies, and source analyses of aerosol optical properties at the SMEAR II measurement station in Hyytiälä, Finland - Virkkula, A.; Backman, J.; Aalto, P. P.; Hulkkonen, M.; Riuttanen, L.; Nieminen, T.; dal Maso, M.; Sogacheva, L.; de Leeuw, G.; Kulmala, M. (Atmospheric Chemistry and Physics, 2011)
Scattering and absorption were measured at the Station for Measuring Ecosystem–Atmosphere Relations (SMEAR II) station in Hyytiälä, Finland, from October 2006 to May 2009. The average scattering coefficient σSP (λ = 550 nm) 18 Mm−1 was about twice as much as at the Pallas Global Atmosphere Watch (GAW) station in Finnish Lapland. The average absorption coefficient σAP (λ = 550 nm) was 2.1 Mm−1. The seasonal cycles were analyzed from hourly-averaged data classified according to the measurement month. The ratio of the highest to the lowest average σSP and σAP was ~1.8 and ~2.8, respectively. The average single-scattering albedo (ω0) was 0.86 in winter and 0.91 in summer. σSP was highly correlated with the volume concentrations calculated from number size distributions in the size range 0.003–10 μm. Assuming that the particle density was 1.5 g cm−3, the PM10 mass scattering efficiency was 3.1 ± 0.9 g m−2 at λ = 550 nm. Scattering coefficients were also calculated from the number size distributions by using a Mie code and the refractive index of ammonium sulfate. The linear regression yielded σSP(modelled) = 1.046 × σSP(measured) for the data with the low nephelometer sample volume relative humidity (RHNEPH = 30 ± 9 %) and σSP(modelled) = 0.985 × σSP(measured) when RHNEPH = 55 ± 4 %. The effective complex refractive index was obtained by an iterative approach, by matching the measured and the modelled σSPand σAP. The average effective complex refractive index was (1.517 ± 0.057) + (0.019 ± 0.015)i at λ = 550 nm. The iterated imaginary part had a strong seasonal cycle, with smallest values in summer and highest in winter. The contribution of submicron particles to scattering was ~90 %. The Ångström exponent of scattering, σSP, was compared with the following weighted mean diameters: count mean diameter (CMD), surface mean diameter (SMD), scattering mean diameter (ScMD), condensation sink mean diameter (CsMD), and volume mean diameter (VMD). If αSP is to be used for estimating some measure of the size of particles, the best choice would be ScMD, then SMD, and then VMD. In all of these the qualitative relationship is similar: the larger the Ångström exponent, the smaller the weighted mean diameter. Contrary to these, CMD increased with increasing αSP and CsMD did not have any clear relationship with αSP. Source regions were estimated with backtrajectories and trajectory statistics. The geometric mean σSP and σAP associated with the grid cells in Eastern Europe were in the range 20–40 Mm−1 and 4–6 Mm−1, respectively. The respective geometric means of σSP and σAP in the grid cells over Norwegian Sea were in the range 5–10 Mm−1 and <1 Mm−1. The source areas associated with high αSP values were norther than those for σSP and σAP. The trajectory statistical approach and a simple wind sector classification agreed well.